Impact of Improving Discipline of Vocational School Students Post Field Work Practice Program (PKL) - Ritantiyo, Toni; Anif, Sofyan; Haryanto, Sigit (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The lack of discipline of post-PKL students at vocational schools requires genuine efforts to maintain academic achievement and preparation for the world of work. This research aims to determine efforts to improve the discipline of vocational school students after the PKL program at SMK MUH 1 Sukoharjo—descriptive qualitative research using the Miles & Huberman method. Data was obtained through non-participant interviews, direct observation, and documentation studies of students, teachers, and SMK MUH 1 Sukoharjo staff. Data analysis includes data reduction, presentation, and conclusion to understand efforts to improve student discipline after PKL. The research found that the PKL program at SMK MUH 1 Sukoharjo was a strategic step in improving student discipline. This can be seen from an increased understanding of discipline application of disciplinary values, to positive changes in students' attitudes and behavior. This positive impact is not only felt in daily life at school but also leads to a significant increase in academic achievement. The PKL program at SMK MUH 1 Sukoharjo has succeeded in creating a learning environment that supports the holistic formation of student character and discipline. In conclusion, the PKL program at SMK MUH 1 Sukoharjo has succeeded in proving its effectiveness in improving student discipline, as seen by increasing understanding of the concept of discipline, application of values, to positive changes in student attitudes and behavior, as well as positive changes in student attitudes and behavior—significant increase in academic achievement.